Spain : IAIS Insurance Core Principles: Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report ;, 2012)
This paper provides an update on the significant regulatory and supervisory development in the Spanish insurance sector since 2006. The Spanish authorities have taken steps to address a number of shortcomings identified in the 2006 Financial Sector Assessment Program. Most notably, cooperation and coordination among the three sectoral supervisors have improved. The paper reveals that despite the lack of independence in the regulatory structure, there is no evidence to suggest that the General Directorate of Insurance and Pension Funds is not independent in carrying out its duties.